RANCANG BANGUN SISTEM INFORMASI PENJUALAN DAN PRIORITAS PENGADAAN BARANG BERBASIS WEB DENGAN METODE PROMETHEE - Fian Hidayah Nurprayogi; Achmad Teguh Wibowo; Mohammad Khusnu Milad (INFORMAL: Informatics Journal, 2019)
This research discussed the usefulness of the promethee method to solve one of the problems that commonly occur in UD Motto Racing Surabaya. Problems at UD. Motto Racing Surabaya which is still using a manual system in determining the priority of procurement. One alternative solution to this problem is to build a system that can directly produce recommendations to determine the priority of procurement. So that it can minimize errors in the re-stock of goods that result in consumers disappointed. With the existence of this sales information system and priority of procurement of web-based, can help leaders in making decisions for the procurement of goods because comfort and customer satisfaction are the main keys to the company. The results obtained are the priority recommendations for the procurement of goods to be more accurate than without using the system, as evidenced from the results of accuracy testing in the number of April percentages of 66.67%, May percentages of 83.33%, June percentages of 50% and July percentages of 83.33%.